Cultural memory in English teaching: a critical autobiographical inquiry. Issue 2 (30th April 2020) - Diamond, Fleur
Abstract : Purpose: Contemporary standards-based reforms to teaching and teacher education are characterised by appeals to technical orientations to teacher professionalism. In addition, the standardisation agenda has targeted literacy education as a focus for interventions. This has highlighted an incongruence between standardised approaches to literacy and pedagogies and practices in subject English that have developed over time, and which represent disciplinary ways of knowing. Design/methodology/approach: This paper uses the occasion of the author's transition from classroom English teacher to teacher educator to inquire into the pedagogies and practices around teaching with texts that form part of her professional identity. The purpose of this study is to introduce cultural memory as an approach to interpreting narratives about educational experience and the development of English pedagogies over time. Findings: The paper argues that standards-based reforms tell "official stories" (Malcolm and Zukas, 2009) about teacher professionalism that displace knowledge of past practices and the ethical and intellectual investments they represent. This is characterised by a marked "presentism" (Green and Cormack, 2015) in contemporary education policy. By contrast, critical autobiographical inquiry practised as cultural memory produces situated accounts of the role of professional memory in the on-going "project" (Green 2002/2014) of English teaching. Originality/value: The paper presents new work in the area of teacher professional identity drawing on the interdisciplinary methods of cultural memory studies.